1972
DOI: 10.1111/j.1365-2133.1972.tb05050.x
|View full text |Cite
|
Sign up to set email alerts
|

Localized Unilateral Hyperhidrosis—a Clinical and Laboratory Study

Abstract: Summary.— Three case of unilateral idiopathic hyperhidrosis are described. Two of the lesions were congenital; the thrid occurred in later life. Quantitative sweat collections demonstrated that the sweat glands in the lesion were hyperresponsive to those stimuli, which normally evoked sweating in the skin sites where the lesions occurred. Hyper‐responsiveness of the sweat glands to cholinergic stimuli was also demonstrated, and histology revealed greatly enalrged glands. These results suggest that the hyperhid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
27
1
1

Year Published

1978
1978
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 7 publications
(1 reference statement)
3
27
1
1
Order By: Relevance
“…It has been demonstrated that sweat glands of the hyperhidrotic area present increased sensitivity against both the muscarinic action of acetylcholine (direct sweat gland stimulation) and the nicotinic action (axon-reflex sweating). These findings are in agreement with the results of Cunliffe et al [1972], The immediate and abundant glandular response to the injected acetylcholine as well as to the nervous impulse eliciting the pheno menon presents similarities with acclimatization and the phenomenon of 'sweat gland training' described by Collins et al [1963]. The end of the hyperhidrotic crisis is attributed primarily to sweat gland fatigue and secondarily to mechanical obstruction of the sweal ducts, resulting from the hydration and swelling of stratum corneum during the crisis [Cunliffe et al, 1972], The mild erythema observed during the phenomenon is evidently due to release of kallikrein by the functioning sweat glands; kallikrein acting on globulins of the tissue fluids produces bradykinin with resultant vasodilation.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…It has been demonstrated that sweat glands of the hyperhidrotic area present increased sensitivity against both the muscarinic action of acetylcholine (direct sweat gland stimulation) and the nicotinic action (axon-reflex sweating). These findings are in agreement with the results of Cunliffe et al [1972], The immediate and abundant glandular response to the injected acetylcholine as well as to the nervous impulse eliciting the pheno menon presents similarities with acclimatization and the phenomenon of 'sweat gland training' described by Collins et al [1963]. The end of the hyperhidrotic crisis is attributed primarily to sweat gland fatigue and secondarily to mechanical obstruction of the sweal ducts, resulting from the hydration and swelling of stratum corneum during the crisis [Cunliffe et al, 1972], The mild erythema observed during the phenomenon is evidently due to release of kallikrein by the functioning sweat glands; kallikrein acting on globulins of the tissue fluids produces bradykinin with resultant vasodilation.…”
Section: Discussionsupporting
confidence: 83%
“…These findings are in agreement with the results of Cunliffe et al [1972], The immediate and abundant glandular response to the injected acetylcholine as well as to the nervous impulse eliciting the pheno menon presents similarities with acclimatization and the phenomenon of 'sweat gland training' described by Collins et al [1963]. The end of the hyperhidrotic crisis is attributed primarily to sweat gland fatigue and secondarily to mechanical obstruction of the sweal ducts, resulting from the hydration and swelling of stratum corneum during the crisis [Cunliffe et al, 1972], The mild erythema observed during the phenomenon is evidently due to release of kallikrein by the functioning sweat glands; kallikrein acting on globulins of the tissue fluids produces bradykinin with resultant vasodilation. This local vasodilator mechanism during the sweat gland activity is still debated [Guyton, 1977], The fact that the erythema was mild in comparison with the intense function of the sweat glands is an indication that this local vasodilator mechanism is of minor capacity and importance.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Frey’s syndrome), associated with diabetes mellitus or parotid diseases [21, 22, 33]. Cutaneous diseases described in association with localized hyperhidrosis include palmoplantar keratodermas, glomus tumor, blue rubber bleb nevus, sudoriferous nevus, POEMS (polyneuropathy, organomegaly, endocrinopathy, M protein, skin changes) syndrome, speckled lentiginous nevus syndrome, Riley-Day syndrome, pachydermoperiostosis, Gopalan syndrome, causalgia, pretibial myxedema, Buerger disease and eccrine pilar angiomatous hamartoma, local injury and increased size of eccrine glands [5,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. LUH, without other cutaneous findings, may occur as a symptom of disease of the central nervous system or peripheral neuropathy, such as stroke, trauma, syringomyelia, tabes dorsalis or pressure on a nerve root caused by a benign or malignant condition such as cervical rib, vertebral osteoma, mesothelioma or pulmonary carcinoma [3, 4,6,7,8,9, 11, 33, 38].…”
Section: Discussionmentioning
confidence: 99%